(untitled) (Czech Journal of International Relations, 2004)
Drawing upon earlier work by the author, the text seeks to help answering the question of the sources of fear regarding the future integration of Slovakia. By looking at the roots and substance of this fear, the author aims to evaluate whether it has become unsubstantiated since the 2002 general election. Even though Dzurinda’s 1998 government has fallen short of the voters’ expectations, this has never been true in the foreign and security policy where the government delivered on its promises. The first chapter aims to identify the key factors, having the greatest effect on the policy- and decision-making of Slovakia’s political elite between 1998 and 2002. These factors have been crucial in extending the country’s image as being the most problematic out of the Visegrad group. The second chapter deals with Slovakia’s internal political watershed: the 1998 general election. The problems weakening and ultimately threatening the ruling coalition from within are analysed as well. The third chapter discusses economic and social aspects of Slovakia’s post-1998 domestic development. The rather unbalanced performance and the lack of achievements are examined as the causes of doubts about the translation of Slovakia’s integration ambitions into practical outcomes. Finally, the last chapter describes the societal perceptions in Slovakia as reflected in public opinion polls prior to the 2002 general election, summing up the election results. In answer to the question posed at the beginning, the author closes his analysis claiming that the current level of preparations for Slovakia’s integration into both the European and Trans-Atlantic structures guarantees that the country will successfully join both. Despite the lack of any bullet-proof guarantee of the stability of the country’s post-2002 political scene, and in spite of potential change of the government or early elections, Slovakia’s full integration into the European and Euro-Atlantic institutional structures in mid-2004 cannot be prevented. Slovakia will join along with its Visegrad partners.